Maternal childbirth experience in induced and spontaneous labour measured in a visual analog scale and the factors influencing it; a two-year cohort study - Katti Adler; Leena Rahkonen; Heidi Kruit (BMC, 2020)
Abstract Background Poor maternal childbirth experience plays a role in family planning and subsequent pregnancies. The aim of this study was to compare childbirth experiences in induced and spontaneous labor and to investigate the factors influencing the childbirth experience. Methods This two-year cohort study included all women with term singleton pregnancies in cephalic presentation aiming for vaginal delivery at Helsinki University Hospital between January 2017 and December 2018. Maternal satisfaction in the childbirth experience was measured after delivery using a Visual Analog Scale (VAS) score. A low childbirth experience score was defined as VAS < 5. The characteristics and delivery outcomes of the study population were collected in the hospital database and analyzed by SPSS. Results A total of 18,396 deliveries were included in the study, of which 28.9% (n = 5322) were induced and 71.1% (n = 13 074) were of spontaneous onset. The total caesarean delivery rate was 9.3% (n = 1727). Overall, 4.5% (n = 819) of the women had a low childbirth experience VAS score. The women who underwent labor induction were less satisfied with their birth experience compared to women with spontaneous onset of labor [7.5% (n = 399) vs. 3.2% (n = 420); p < 0.001]. Poor childbirth experience was associated with primiparity [OR 2.0 (95% CI 1.6-2.4)], labor induction [OR 1.6 (95% CI 1.4-1.9)], caesarean delivery [OR 4.5 (95% CI 3.7-5.5)], operative vaginal delivery [OR 3.3 (95% CI 2.7-4.0)], post-partum hemorrhage [OR 1.3 (95% CI 1.1-1.6)], and maternal infections [OR 1.7 (95% CI 1.3-2.4)]. Conclusions Poor childbirth experience was associated with labor induction, primiparity, operative delivery, and labor complications, such as post-partum hemorrhage and maternal infections. These results highlight the aspects of care for which patient experience may be improved by additional support and counselling.